A Rising Edge-Based Detection Algorithm for MIMO Molecular Communication - Huang, Yu; Chen, Xuan; Wen, Miaowen; Yang, Lie-Liang; Chae, Chan-Byoung; Ji, Fei (IEEE wireless communications letters, 2020)
In this letter, we propose a low-complexity detection algorithm for multi-input-multi-output (MIMO) molecular communication (MC). By virtue of a rising edge in received signals, this detection algorithm is capable of recovering the information bits in MIMO-MC systems. From an engineering point of view, this algorithm can significantly eliminate the impact of inter-symbol interference. It has also proven itself useful for dealing with the received signal from the MIMO-MC testbed with sufficiently low bit error rate (BER) or even an error-free performance. Moreover, in terms of BER performance, this algorithm outperforms existing detection algorithms for single-input single-output MC systems.